Morbilidad asociada al embarazo en las pacientes atendidas en el Centro de Salud Dra. Mabel Estupiñán en el período enero del 2009 a diciembre del 2009 - Feijoó Sigcho, Rosa P. (2011)
Women on their pregnancy period can show a lot of pathologies of their own state, which are product of physiological and educative causes, and for the in El Oro province, is unknown works or researches which show us the frequency of these on pregnant women who go to private or public health services.